THE RELATIONSHIP BETWEEN EFFECTIVENESS OF BREASTFEEDING WITH THE INCIDENCE OF PHYSIOLOGIC HYPERBILIRUBINEMIA IN NEONATAL MATURE AGE OF 2-4 DAYS - Mayrita Syam (Journal of Maternity Care and Reproductive Health, 2021)
Newborn who receive initation of breastfeeding effectively and colostrum is believed to reduce incidence of physiologic hyperbilirubinemia. breastfeeding.The purpose of this study was to the effectiveness of breastfeeding relationship with the incidence of physiologic hyperbilirubinemia in infants mature age of 2-4 days.This study uses a descriptive quantitative analytic method with a cross-sectional approach. Data were taken from the baby room of RSIA UMMI Bogor in November 2015. Respondents from this study were all mothers of infants and hyperbilirubinemic infants who met the inclusion criteria. The sampling technique was total sampling, namely all members of the population were used as a sample of 30 respondents. Data collection using a questionnaire. The data analysis used univariate analysis which was presented in the frequency distribution table while the bivariate data used the chi-square test. From the results of the study, it was found that the effectiveness of breastfeeding with the incidence of hyperbilirubinemia where out of 12 (40%) mothers who were ineffective in breastfeeding their babies experienced hyperbilirubinemia. And based on the chi-square test, there was a relationship between the effectiveness of breastfeeding and the incidence of hyperbilirubinemia (p = 0.027). The effectiveness of breastfeeding can reduce the incidence of hyperbilirubin in infants. The faster and more often the mother gives breast milk to her baby, the faster and more milk production will be to meet nutritional intake The important role of health workers in the success of breastfeeding or breastfeeding, should add knowledge about lactation, so that it can help post partum mothers if there are problems with breastfeeding. There is also a need for a professional breastfeeding counselor in dealing with breastfeeding problems.